Analisis Pengaruh Produksi dan Luas Lahan Kelapa Sawit terhadap PDRB Sektor Pertanian: Pendekatan Regresi Linier Berganda menggunakan Data Sekunder 2013-2022 - Said, Anwar; Akhmad, Akhmad; Sribianti, Irma; Natsir, Mohammad; Maulina, Maulina (LP3M, Universitas Muhammadiyah Kendari, 2024)
The issue in this research is that the increase and decrease of agricultural GDP per capita in Southeast Sulawesi are significantly influenced by several factors, one of which is the production factor and the availability of land for oil palm cultivation. Therefore, an analysis is needed regarding the impact of GDP on the production and land area of oil palm in Southeast Sulawesi. This study aims to understand the impact of oil palm production and cultivated area on the Gross Regional Domestic Product (GRDP) of the agricultural sector in Southeast Sulawesi Province. The sample for this study uses secondary data derived from the Southeast Sulawesi Provincial Statistics Agency and the Indonesian Palm Oil Statistics Book from 2013 to 2022. This research is analyzed using multiple linear regression methods with IBM SPSS Statistics 25 software. The results of this study indicate that oil palm production in the Southeast Sulawesi region has a negative and significant effect on the agricultural GRDP of Southeast Sulawesi, while the expansion of oil palm plantation area has a positive and significant effect on the agricultural sector GRDP in Southeast Sulawesi Province.